Nanostructured Architectures for Biomolecular Detection inside and outside the Cell. (3rd December 2019) - Chen, Jenise B.; Yousefi, Hanie; Nemr, Carine R.; Gomis, Surath; Atwal, Randy; Labib, Mahmoud; Sargent, Edward; Kelley, Shana O.
Abstract: Nanostructured materials can now be engineered with great precision and complexity as a result of advances in design and fabrication, and offer distinct advantages in many biosensing and biomedical applications. The materials most widely used in this field are semiconductors and noble metals. Each offers multiple length scales of nanostructuring that program their physicochemical properties for different biosensing applications. Here, nanostructured materials and their applications are reviewed together with semiconductors and noble metals, as well as hybrid materials that unite these two classes—all with the goal of linking performance characteristics to applications in biomedicine. Abstract : Nanostructured materials are now ubiquitous functional elements in biomolecular sensors. Herein, semiconductor and noble metal nanomaterials used successfully to develop new biomolecular detection capabilities for in vitro, in vivo, intracellular, and extracellular sensing are reviewed. Structural characteristics that can be directly linked with performance enhancements are highlighted to showcase the rationale for using nanomaterials in biomedical applications.